Impact of matrix–fracture interactions on coal permeability: Model development and analysis - Liu, Ting; Lin, Baiquan; Yang, Wei (Fuel (Guildford), 2017)
•A new permeability model considering the matrix–fracture interaction is developed.•The influencing factors of internal swelling coefficient are discussed.•The effect of internal swelling coefficient on coal permeability is explored. In this study, we develop a new permeability model that incorporates the matrix–fracture interactions. In addition, a newly defined internal swelling coefficient (f) has been introduced to quantify the contribution of adsorption-induced matrix deformation to fracture aperture and coal permeability. The model is independent of the boundary conditions and has been verified with the data tested under the conditions of uniaxial strain, constant external stress, constant effective stress, and constant pore pressure. Besides, a comparison between the commonly used models and our model shows that our model can cover most of the variation trends of the other models. The influencing factors and the mechanisms controlling the internal swelling coefficient have been comprehensively discussed. The results show that under the conditions of uniaxial strain and constant effective stress, f shows a downward trend with a reduction of the pore pressure, whereas under the constant external stress condition, f presents an opposite variation trend. The gas type has an effect on the internal swelling coefficient and f decreases in the order of N2, CH4, and CO2. In addition, the coal type also affects the internal swelling coefficient. All the factors indirectly affect the internal swelling coefficient by changing the effective stress and adsorption-induced matrix deformation. We have also investigated the controlling mechanism of the internal swelling coefficient on permeability, which indicated that the permeability shows an opposite variation trend with the internal swelling coefficient. It is suggested that the internal swelling coefficient can be set as a value in the range of 0–0.2 for the prediction of coal seam permeability during CBM recovery and CO2 geological sequestration.